Order equivalent equations of 2(x – 3) = 4x to solve for x.
2x – 6 = 4x
-3 = 2x
-3 = x
-6 = 2x
2x – 3 = 4x
-3/2 = x
Share
Lost your password? Please enter your email address. You will receive a link and will create a new password via email.
Please briefly explain why you feel this question should be reported.
Please briefly explain why you feel this answer should be reported.
Please briefly explain why you feel this user should be reported.
To solve the equation (2(x – 3) = 4x), let’s first simplify it step by step:
1. Distribute the 2:
[
2x – 6 = 4x
]
2. Rearrange the equation:
Subtract (2x) from both sides:
[
-6 = 4x – 2x
]
This simplifies to:
[
-6 = 2x
]
3. Divide both sides by 2 to isolate (x):
[
x = -3
]
Now, let’s check the equivalent equations provided:
– (2x – 6 = 4x) is correct.
– (-3 = 2x) can be rearranged to get (x = -3); this is also correct.
– (-3 = x) is not equivalent, as we found (x = -3) but this format isn’t foundationally sound since it suggests a contradiction.
– (-6 = 2x) is correct and leads to the same conclusion.
– (2x – 3 = 4x) does not hold true based on the original equation as it’s derived differently.
– (-frac{3}{2} = x) is incorrect based on the solved value.
Therefore, the correct